TRAMWAY MANAGEMENT SYSTEM IN INDONESIA - Melia Damayanti; Siti Malkhamah; Karen Walker (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2015)
Tramway systems, which can carry more passengers than buses at one haul, are now being proposed to meet Indonesia’s public transport requirement. The objective of this research is to analyze the management structures for operating tram in different countries and then propose a suitable organizational structure for operating trams, if re-introduced, in Indonesia. The author chose France (Montpellier tramway), Germany (Karlsruhe tram-train) and the UK (Nottingham Express Transit) as the role model countries for investigation. From the analysis, the most appropriate organizational structure and suitable tramway management structure for operating tramways implementation in Indonesia. The key features of the research are to establish public transport company by local government to manage all public transport systems, propose tramway construction and operation to exist as separate departments under the tramway team division of the public company, recommend the public transport company to have responsibility for overseeing construction of the trams, operating, and maintaining the trams, suggest local government to own them and have responsibility for tramway strategic policy, control regulation as well as supervision and coordination of the performance of the public transport company, propose joint working between public and private sectors.